Excursion Report: Kepulauan Seribu Field Trip - Modern Carbonate Depositional Environment in the Outline of Jakarta - Muhammad T. Gandaprana; Taufan Tryastono; Muhammad Irwan Pernando; Achmad Chaidar (Berita Sedimentologi, 2016)
In February 2015, the Padjadjaran University (Universitas Padjadjaran - UNPAD) Sedimentology Research Team held an excursion to Kepulauan Seribu (Thousand Islands) in the Java Sea, offshore northern Jakarta. The trip was not just about having fun and luxurious escape, but more importantly it was to enjoy the adventure with pocket-friendly expenses and gain new geological knowledge directly from the field. For a team that comprises young geologists, every side of the earth is interesting especially in relatively remote areas where earth processes’ imprints are preserved better; the geological phenomena can be traced back to its formation in the past and deduced of the impact in the future.